Visible-light-activated copper(i) catalyzed oxidative Csp–Csp cross-coupling reaction: efficient synthesis of unsymmetrical conjugated diynes without ligands and base. Issue 16 (6th July 2016) - Sagadevan, Arunachalam; Lyu, Ping-Chiang; Hwang, Kuo Chu
Abstract : An efficient and eco-friendly approach to Csp –Csp cross-coupling of terminal alkynes for the construction of unsymmetrical conjugated diynes via a visible-light-induced CuCl catalysed process at room temperature is described. Abstract : A novel visible-light-promoted copper-catalysed process for the Csp –Csp cross-coupling reaction of terminal alkynes at room temperature is described. The current photochemical method is simple, highly functional group compatible, and more viable towards the construction of bio-active 1, 3-unsymmetrical conjugated diynes without the need of bases/ligands, additives and expensive palladium/gold catalysts.